2022
DOI: 10.1021/acs.jpclett.2c03186
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Pressure-Axis Experiments to Explore Volume Fluctuations, Conformational Substates, and Solvation of Biomolecular Systems

Abstract: Intrinsic thermodynamic fluctuations within biomolecules are crucial for their function, and flexibility is one of the strategies that evolution has developed to adapt to extreme environments. In this regard, pressure perturbation is an important tool for mechanistically exploring the causes and effects of volume fluctuations in biomolecules and biomolecular assemblies, their role in biomolecular interactions and reactions, and how they are affected by the solvent properties. High hydrostatic pressure is also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 105 publications
0
12
0
Order By: Relevance
“…The application of pressure has the potential to yield additional information about the prevalent intermolecular forces underlying the aggregate formation as the balance between hydrogen bonding, electrostatic and hydrophobic intra- and intermolecular interactions can be tuned by pressure modulation. H-bonds are generally strengthened upon pressurization, whereas salt bridges are destabilized by high pressure. The dissociation of protein aggregates and unfolding of proteins are also due to the existence of internal voids and packing defects of these structures, leading, in accordance with Le Châtelier’s principle, to an overall volume decrease upon unfolding. ,,, The abundance of ionic interactions between K n and ATP within the aggregates is expected to render them sensitive to high pressure due to the phenomenon of electrostriction ( i.e. , polar water molecules being packed more tightly around separated charges than around nondissociated salt bridges), i.e.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The application of pressure has the potential to yield additional information about the prevalent intermolecular forces underlying the aggregate formation as the balance between hydrogen bonding, electrostatic and hydrophobic intra- and intermolecular interactions can be tuned by pressure modulation. H-bonds are generally strengthened upon pressurization, whereas salt bridges are destabilized by high pressure. The dissociation of protein aggregates and unfolding of proteins are also due to the existence of internal voids and packing defects of these structures, leading, in accordance with Le Châtelier’s principle, to an overall volume decrease upon unfolding. ,,, The abundance of ionic interactions between K n and ATP within the aggregates is expected to render them sensitive to high pressure due to the phenomenon of electrostriction ( i.e. , polar water molecules being packed more tightly around separated charges than around nondissociated salt bridges), i.e.…”
Section: Resultsmentioning
confidence: 92%
“…The dissociation of protein aggregates and unfolding of proteins are also due to the existence of internal voids and packing defects of these structures, leading, in accordance with Le Chatelier's principle, to an overall volume decrease upon unfolding. 34,35,40,41 The abundance of ionic interactions between K n and ATP within the aggregates is expected to render them sensitive to high pressure due to the phenomenon of electrostriction (i.e., polar water molecules being packed more tightly around separated charges than around nondissociated salt bridges), i.e., high pressure favors the dissociation of ion pairs and therefore the disassembly of supramolecular architectures that they support. Packing defects in the more disordered K 40 oligolysine/ATP system, as revealed by the FT-IR data, might contribute to the highpressure sensitivity as well.…”
Section: Resultsmentioning
confidence: 99%
“…From the pressure dependence of K b , it was possible to calculate the volume change accompanying the complexation reaction, [25,26] according to (dln K b /d p ) T = - ${-}$ Δ V b °/( RT ), where Δ V b ° is the binding volume, which is defined as the difference between the partial molar volume of the ligand‐protein complex and the sum of the partial molar volumes of the ligand and of the protein. According to the Le Châtelier principle, pressure favors the state that occupies the smallest possible overall volume [15,25,26] . Thus, if pressure favors the formation of the complex, Δ V b ° will be negative, and vice versa.…”
Section: Resultsmentioning
confidence: 99%
“…The high‐pressure binding data revealed that the binding volume (Table 1) for the interaction of EA with BSA is positive, indicating that the complex occupies a larger volume with respect to the uncomplexed state. A Δ V b °>0 can be ascribed to an increase of void volume in the binding pocket upon complex formation and/or the release of hydration water to the bulk solvent [15,18,25] . Instead, for IB7‐14, the binding volume is essentially zero, revealing an almost perfect packing between the interacting partners.…”
Section: Discussionmentioning
confidence: 99%
“…At appropriate concentrations, PEG and dextran spontaneously separate, 238 forming droplets enriched in dextran dispersed in a solution of PEG. 44,239,240 The protein BSA and ANS preferentially localize in the dextran-enriched droplets, where the polymer concentration is around 30 wt %. HHP fluorescence spectroscopy binding experiments showed that on average three molecules of ANS molecules bind to one BSA macromolecule (Figure 36B), both at neat buffer conditions and in the ATPS system at ambient pressure.…”
Section: Ligand Bindingmentioning
confidence: 99%